PERAN GURU BIMBINGAN DAN KONSELING DALAM MENUMBUHKEMBANGKAN MINAT PESERTA DIDIK UNTUK MENGIKUTI KEGIATAN EKSTRA KURIKULER DI SMA NEGERI 1 SITIUNG - Haumi, Naufil; Kasih, Fitria; Zaini, Ahmad (Bimbingan dan Konseling, 2013)
This research is motivated by character of counselor teachers to create learnersâ interesting to do extra curriculer activities. This research aims to describe : character of counselor teachers to create learnersâ interesting to do extra curriculer at SMAN 1 Sitiung. That be seen from: 1) affectiveâs aspect 2) psikomotorâs aspect 3) cognitiveâs aspect. This research is descriptive study. Population in this research are all of learners in SMAN 1 Sitiung. Concluded sampel with random sampling, it consist of 83 learners. Instrument that used in this research is inquiry and tehnique analysis data were collected by percentage technique. The result of research are: 1) character of counselor teachers in create learnersâ interesting to do extra curriculer that be seen from affectiveâs aspect is good enough , 2) character of counselor teachers in create learnersâ interesting to do extra curriculer that be seen from psikomotorâs aspect is good enough, 3) character of counselor teachers in create learnersâ interesting to do extra curriculer that be seen from cognitiveâs aspect is good enough. Researcher give recommandation to all of counselor teachers, as a program to do their character at school to help them in create learnersâ interesting in extra curriculerÂ  activities.